Climate Change–Induced Stress Reduce Quantity and Alter Composition of Nectar and Pollen From a Bee-Pollinated Species (Borago officinalis, Boraginaceae) - Descamps, Charlotte; Quinet, Muriel; Jacquemart, Anne-Laure (Frontiers in Plant Science, 2021)
In temperate ecosystems, elevated temperatures and drought occur especially during spring and summer, which are crucial periods for flowering, pollination and reproduction of a majority of temperate plants. While many mechanisms may underlie pollinator decline in the wake of climate change, the interactive effects of temperature and water stress on the quantity and quality of floral nectar and pollen resources remain poorly studied. We investigated the impact of temperature rise (+3 °C and +6 °C) and water stress (soil humidity lower than 15%) on the floral resources produced by the bee-pollinated species Borago officinalis. Nectar volume decreased with both temperature rise and water stress (6.1 +- 0.5 µl per flower under control conditions, 0.8 +- 0.1 µl per flower under high temperature and water stress conditions), resulting in a 60% decrease in the total quantity of nectar sugars (mg) produced per flower. Temperature rise but not water stress also induced a 50% decrease in pollen weight per flower but a 65% increase in pollen polypeptide concentration. Both temperature rise and water stress increased the total amino acid concentration and the essential amino acid percentage in nectar but not in pollen. In both pollen and nectar, the relative percentage of the different amino acids were modified under stresses. We discuss these modifications in floral resources in regards to plant–pollinator interactions and consequences on plant pollination success and on insect nutritional needs.